Circulating plasma phospholipid fatty acid levels and breast cancer risk in the Cancer Prevention Study‐II Nutrition Cohort. Issue 12 (5th September 2022) - Matta, Michèle; Deubler, Emily; Chajes, Veronique; Vozar, Beatrice; Gunter, Marc J.; Murphy, Neil; Gaudet, Mia M.
Abstract: Prospective studies that objectively measure circulating levels of fatty acids are needed to clarify their role in the etiology of breast cancer. Thirty‐eight phospholipid fatty acids were measured using gas chromatograph in the plasma fraction of blood samples collected prospectively from 2718 postmenopausal women (905 breast cancer cases) enrolled in the Cancer Prevention Study II Nutrition Cohort. Associations of 28 fatty acids that passed quality control metrics (modeled as per 1‐SD increase) with breast cancer risk were assessed using multiple variable conditional logistic regression models to compute odds ratios (OR) and 95% confidence intervals (CI). The false discovery rate ( q value) was computed to account for multiple comparisons. Myristic acid levels were positively associated with breast cancer risk (OR, 1.17, 95% CI: 1.07‐1.28; q value = 0.03). Borderline associations were also found for palmitoleic acid (OR, 1.14, 95% CI: 1.04‐1.24) and desaturation index16 (OR, 1.10, 95% CI: 1.01‐1.20) at nominal P values (<.03) ( q values>0.05). These findings suggest that higher circulating levels of myristic acid, sourced from dietary intake of palm kernel oils along with increased de novo synthesis of fatty acids, may increase breast cancer risk. Additional studies are needed to investigate de novo synthesis of fatty acid in breast cancer tissues. Abstract : What's new? While dietary intake of fatty acids may influence breast cancer development, associations with body size and hormone receptor subtypes of disease remain uncertain. Here, using blood samples collected from postmenopausal women, the authors investigated relationships between breast cancer risk and circulating levels of specific phospholipid fatty acids. Analyses show that breast cancer risk is positively associated with increased circulating levels of myristic acid. Levels of palmitoleic acid were weakly associated with risk. The results identify a role for specific phospholipid fatty acids in breast cancer etiology and lend support to future studies to inform nutritional strategies for breast cancer prevention.